Differential regulation of two types of monogalactosyldiacylglycerol synthase in membrane lipid remodeling under phosphate-limited conditions in sesame plants - Shimojima, Mie; Watanabe, Takahide; Madoka, Yuka; Koizumi, Ryota; Yamamoto, Masayuki P.; Masuda, Kyojiro; Yamada, Kyoji; Masuda, Shinji; Ohta, Hiroyuki (Frontiers in Plant Science, 2013)
Phosphate (Pi) limitation causes drastic lipid remodeling in plant membranes. Glycolipids substitute for the phospholipids that are degraded, thereby supplying Pi needed for essential biological processes. Two major types of remodeling of membrane lipids occur in higher plants: whereas one involves an increase in the concentration of sulfoquinovosyldiacylglycerol in plastids to compensate for a decreased concentration of phosphatidylglycerol, the other involves digalactosyldiacylglycerol (DGDG) synthesis in plastids and the export of DGDG to extraplastidial membranes to compensate for reduced abundances of phospholipids. Lipid remodeling depends on an adequate supply of monogalactosyldiacylglycerol (MGDG), which is a substrate that supports the elevated rate of DGDG synthesis that is induced by low Pi availability. Regulation of MGDG synthesis has been analyzed most extensively using the model plant Arabidopsis thaliana, although orthologous genes that encode putative MGDG synthases exist in photosynthetic organisms from bacteria to higher plants. We recently hypothesized that two types of MGDG synthase diverged after the appearance of seed plants. This divergence might have both enabled plants to adapt to a wide range of Pi availability in soils and contributed to the diversity of seed plants. In the work presented here, we found that membrane lipid remodeling also takes place in sesame, which is one of the most common traditional crops grown in Asia. We identified two types of MGDG synthase from sesame (encoded by SeMGD1 and SeMGD2) and analyzed their enzymatic properties. Our results show that both genes correspond to the Arabidopsis type-A and -B isoforms of MGDG synthase. Notably, whereas Pi limitation up-regulates only the gene encoding the type-B isoform of Arabidopsis, low Pi availability up-regulates the expression of both SeMGD1 and SeMGD2. We discuss the significance of the different responses to low Pi availability in sesame and Arabidopsis.